Efektivitas Pembelajaran Outdoor Study Terhadap Pemahaman Konsep IPA Siswa Kelas VII Mts Darul Ulum Kota Ternate - Usman, Asyhari; ., Faradina (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2025)
Science learning requires students to develop a deep understanding of concepts through direct engagement with their environment. However, classroom instruction still predominantly employs conventional approaches that provide limited contextual experiences. This condition can hinder students’ ability to connect theoretical knowledge with real-world environmental phenomena. Therefore, innovation in learning activities is needed to enhance students conceptual understanding, one of which is through the implementation of outdoor study learning. This study aims to analyze the effectiveness of outdoor study learning in improving science conceptual understanding among Class VII students at MTs Darul Ulum, Kota Ternate. This research employed a pre-experimental design using a one-group pretest–posttest model. The sample consisted of 29 students selected through purposive sampling. Data were collected through observation, interviews, science concept understanding tests, and documentation. The data analysis techniques included normality testing, paired sample t-test at a significance level of <0.05, and N-Gain analysis. The results of the paired t-test indicated a significant difference between students’ pretest and posttest scores, with the mean pretest score of 66 increasing to a posttest mean score of 98, and a significance value (Sig. 2-tailed) of 0.000 < 0.05. The N-Gain value of 0.76 categorized the learning as effective. Based on these findings, it can be concluded that the implementation of outdoor study learning is effective in improving students’ conceptual understanding of science. Therefore, outdoor study can be considered an innovative and contextually rich approach to be applied in science education, promoting students’ scientific literacy and meaningful learning experiences.